On the influence of topographic, geological and cryospheric factors on rock avalanches and rockfalls in high-mountain areas - L. Fischer; R. S. Purves; C. Huggel; J. Noetzli; W. Haeberli (Natural Hazards and Earth System Sciences, 2012)
The ongoing debate about the effects of changes in the high-mountain cryosphere on rockfalls and rock avalanches suggests a need for more knowledge about characteristics and distribution of recent rock-slope instabilities. This paper investigates 56 sites with slope failures between 1900 and 2007 in the central European Alps with respect to their geological and topographical settings and zones of possible permafrost degradation and glacial recession. Analyses of the temporal distribution show an increase in frequency within the last decades. A large proportion of the slope failures (60%) originated from a relatively small area above 3000 m a.s.l. (i.e. 10% of the entire investigation area). This increased proportion of detachment zones above 3000 m a.s.l. is postulated to be a result of a combination of factors, namely a larger proportion of high slope angles, high periglacial weathering due to recent glacier retreat (almost half of the slope failures having occurred in areas with recent deglaciation), and widespread permafrost occurrence. The lithological setting appears to influence volume rather than frequency of a slope failure. However, our analyses show that not only the changes in cryosphere, but also other factors which remain constant over long periods play an important role in slope failures.